Controlled deposition of human neural stem cells on fiber substrates using gel encapsulation - Carl-Johan Hörberg; Martin Arvidsson; Axel Sandberg; David O’Carroll; Fredrik Johansson; Ulrica Englund Johansson (PLoS ONE, 2026)
Electrospinning is a versatile technique for manufacturing micro-nano diameter fibers and has been used extensively for tissue engineering in vivo and advanced cell culture in vitro. Standard means of seeding cells onto such substrates typically offer no control over cell distribution, yielding dispersed, heterogeneous and low concentrations of cells. In this article, we investigate the viability of using a simple bioprinting-inspired device for seeding gel-encapsulated cells onto fiber substrates. Using human neural stem cells, we were able to consistently seed cells with spatial control. We examined their long-term development, showing viable cells and normal differentiation potential. Furthermore, this device was able to seed on multiple sites within a single substrate, creating isolated populations and demonstrating the potential for this approach as a low-cost alternative to bioprinting systems, which is also applicable to somewhat challenging 3D substrates like electrospun fibers.